Penguatan Strategi Pemasaran Digital Masyarakat Baduy Luar: Analisis Dinamika Ekonomi dalam Perspektif Kebutuhan Fisiologis Maslow - Ruth Margaretha; Ainissifa; Catharina Nicole (Inisiatif : Jurnal Dedikasi Pengabdian Masyarakat, 2026)
The economic dynamics of the Baduy Luar community in meeting basic needs, amid the limitations of a traditional economic system based on agriculture and weaving, have encouraged the emergence of trading activities as a form of economic adaptation without abandoning the customary values that are still upheld by the community. The purpose of this activity is to analyze the economic dynamics of the Baduy Luar community from the perspective of Maslow’s hierarchy of needs, as well as to provide education on digital marketing strategies as an alternative to strengthen the community’s economy. The method used in this community service activity is Participatory Action Research (PAR) with a participatory approach through observation, discussion, education, consultation, and simple assistance related to the use of digital media in product marketing. The activity was conducted over three days involving five informants who are actively engaged in trading activities. The results of the activity show that the Baduy Luar community has begun to understand the importance of digital marketing through media such as WhatsApp and online marketplaces to expand the reach of product sales. In addition, the activity indicates that the community has a relatively strong capacity for economic adaptation, as long as the changes made remain aligned with their customary values.